Study of Key Commodity Aspects of Injection Pens for Insulin Administration and Needles for Them - Diadiun, Tatiana V. (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Diabetes mellitus is a disease which is the most common cause of early disability and high mortality. One of the most effective treatments for diabetes is insulin therapy. The treatment is carried out using different types of insulin produced by the pharmaceutical industry. However, any such preparations are always a solution, which must be introduced with a device. Materials and Methods: Analysis of the State Register of medical equipment and medical products: Injection pens for insulin and needles for them of different brands that are most used to treat diabetes patients. Results and Discussion: Today on the world market, there are numerous devices that are used to deliver insulin into the body, including the special syringes, insulin pumps, injection pens, and more. Today, such a device as injection pen (autoinjector) is the most convenient for insulin administration. In the Ukrainian market, there are syringe-pens of mostly foreign origin. Conclusion: Use can increase compliance that increases the acceptability of treatment (ease of use, less pain) and improve blood glucose control.